2004
DOI: 10.1001/jama.291.8.965
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate for Migraine Prevention<SUBTITLE>A Randomized Controlled Trial</SUBTITLE>

Abstract: TN 37203 (jbrandes @nashvilleneuroscience.com).Context Small open-label and controlled trials suggest that the antiepileptic drug topiramate is effective for migraine prevention.Objective To assess the efficacy and safety of topiramate for migraine prevention in a large controlled trial. Design, Setting, and PatientsA 26-week, randomized, double-blind, placebocontrolled study was conducted during outpatient treatment at 52 North American clinical centers. Patients were aged 12 to 65 years and had a 6-month his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
537
6
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(583 citation statements)
references
References 30 publications
33
537
6
7
Order By: Relevance
“…Interestingly, among the group of responders in long-term treatment there was only one patient whose headaches became worse while on topiramate. Adverse events were similar to those seen in previous clinical trials with topiramate [11][12][13]. None of these patients discontinued the drug due to unbearable adverse events in the first two years of treatment.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, among the group of responders in long-term treatment there was only one patient whose headaches became worse while on topiramate. Adverse events were similar to those seen in previous clinical trials with topiramate [11][12][13]. None of these patients discontinued the drug due to unbearable adverse events in the first two years of treatment.…”
Section: Discussionsupporting
confidence: 82%
“…We analyzed dose-response associations and found that an increase in target topiramate dose from 50 to 100 mg/day but not from 100 to 200 mg/ day resulted in a higher response rate (≥50 % reduction in monthly migraine frequency). [72][73][74] Approved drugs improved other patient-centered outcomes in addition to monthly migraine frequency. Topiramate improved quality of life measured by scores on the Headache Impact Test, 75 Migraine-Specific Questionnaire, 76 and Migraine Disability Assessment.…”
Section: Resultsmentioning
confidence: 99%
“…78 Divalproex in a larger dose of 1,500 mg/day increased the likelihood of a >50 % improvement in whether migraine attacks impaired usual activities or necessitated symptomatic medication and in reducing migraine attacks with nausea, vomiting, phonophobia, or photophobia. 79 Topiramate 73,74,[80][81][82] and propranolol decreased use of drugs for acute migraine attacks. 83 Among off-label drugs, pooled analyses offered lowstrength evidence that the beta-blocker metoprolol (approved for migraine prevention in Europe) and calcium channel blocker nimodipine were better than placebo in reducing monthly migraine attacks by ≥50 % ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Also lamotrigine, a sodium channel blocker with antiglutamatergic actions, seemed highly effective in reducing migraine aura and migraine attacks in a controlled open study (Lampl et al 2005). Similarly, the anticonvulsant topiramate is effective in migraine prophylaxis (Brandes et al 2004;Diener et al 2004;Silberstein et al 2004). This effect may be mediated by blockade on voltage-activated Na + and Ca 2+ channels and/or blockade of AMPA and kainate receptors.…”
Section: Glutamate Receptorsmentioning
confidence: 99%